The early-type galaxy population in Abell 2218 - Ziegler, B; Bower, R; Smail, I; Davies, R; Lee, D (2001)
(Abridged) We present morphological, photometric, kinematic and line-strength data of 48 early-type members of the rich cluster Abell 2218 at z=0.18. This sample is both larger and spans a wider galaxy luminosity range, down to M*_B+1, than previous studies. We compare A2218 with similar samples drawn from local clusters to identify evolutionary changes between the samples which have occured over the last 3Gyrs. The overall picture is one of little or no evolution in nearly all galaxy parameters. Zeropoint offsets in the Faber--Jackson, Mg_b-sigma and Fundamental Plane relations are all consistent with passively evolving stellar populations. The slopes of these relations have not changed significantly. We do however find a significant spread in the estimated luminosity-weighted ages of the stellar populations in the galaxies, based on line diagnostic diagrams. This age spread is seen in both the disky early-type galaxies (S0) and also the ellipticals. We observe both ellipticals with a strong contribution from a young stellar population and lenticulars dominated by old stellar populations. On average, we find no evidence for systematic differences between the populations of ellipticals and lenticulars. This points to a common formation epoch for the bulk of the stars in most of the early-type galaxies in A2218. This result can be reconciled with the claims of rapid morphological evolution in distant clusters if the suggested transformation from spirals to lenticulars does not involve significant new star formation.